The vegetable gardener's guide to permaculture : creating an edible ecosystem - Shein, Christopher (Timber Press, 2013)
The Vegetable Gardener's Guide to Permaculture teaches gardeners of every skill -- with any size space -- how to live in harmony with both nature and neighbors to produce and share an abundant food supply with minimal effort. Permaculture teacher Christopher Shein highlights everything you need to know to start living off the land lightly, including how to create rich, healthy, and low-cost soil, blend a functional food garden and decorative landscape, share the bounty with others, and much more.